2009
DOI: 10.1158/0008-5472.can-08-1753
|View full text |Cite
|
Sign up to set email alerts
|

Translymphatic Chemotherapy by Intrapleural Placement of Gelatin Sponge Containing Biodegradable Paclitaxel Colloids Controls Lymphatic Metastasis in Lung Cancer

Abstract: As a means of treating lymphatic metastasis from lung cancer, the pharmacokinetics and therapeutic effects of an intrapleural (ipl) implantable drug delivery system consisting of a gelatin sponge impregnated with polylactide-co-glycolide paclitaxel (PLGA-PTX) microspheres were studied. PLGA-PTX with 7% (w/w) drug loading were incorporated into gelatin matrix. The pharmacokinetics were studied in rats with one of the following regimens: (a) Taxol 8 mg/kg by i.v. injection; (b) Taxol 8 mg/kg ipl; (c) PLGA-PTX (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…29 To date, studies focusing on the intrapleural delivery of nanomedicine have been very rare, but the results have shown favorable control of lung cancer. 30 The results of the current study may consolidate these published findings and could trigger more research on the intrapleural delivery of nanomedicine for the control of primary or secondary lung cancer.…”
supporting
confidence: 74%
“…29 To date, studies focusing on the intrapleural delivery of nanomedicine have been very rare, but the results have shown favorable control of lung cancer. 30 The results of the current study may consolidate these published findings and could trigger more research on the intrapleural delivery of nanomedicine for the control of primary or secondary lung cancer.…”
supporting
confidence: 74%
“…Shikanov, et al, injected a semiliquid extended release polymer loaded with Paclitaxel to an orthotopic R3327 rat prostate tumor, which inhibited the prostate tumor and its metastasis to lung and lymph nodes for 25 days [28]. Liu, et al, placed a gelatin sponge with PLGA microspheres containing Paclitaxel near orthotopic rat lung cancer, and found that during a 14 -32 day period, the mediastinum lymph nodes have higher area under the curve AUC drug and fewer metastatic tumors than IV treated tumors [31]. Both of the two studies bear similarities to our report.…”
Section: An Ideal Pharmacological Paradigm Achievablementioning
confidence: 99%
“…Paclitaxel (PTX) is one of the most potent anticancer drugs, and is widely used in the therapy of NSCLC. 9,10 Nevertheless, the clinical use of PTX is limited by poor aqueous solubility, high toxicity, and low bioavailability. 11 Taxol is one of the formulations of PTX that can be used in the therapy of NSCLS.…”
Section: Introductionmentioning
confidence: 99%